Biological activity of bis(pyrazolylpyridine) and terpiridine Os(ii) complexes in the presence of biocompatible ionic liquids. Issue 11 (16th April 2021) - Petrović, Angelina Z.; Ćoćić, Dušan C.; Bockfeld, Dirk; Živanović, Marko; Milivojević, Nevena; Virijević, Katarina; Janković, Nenad; Scheurer, Andreas; Vraneš, Milan; Bogojeski, Jovana V.
Abstract : New bis(pyrazolylpyridine) Os(ii ) complexes showing possible biological activity with diverse modes of action in the presence of biocompatible ionic liquids as non-toxic cosolvents for sparingly soluble complexes. Abstract : Within this paper is presented the synthesis and structural characterization of three newly synthesized osmium(ii ) complexes Os1–3, with the chemical formula [Os II LCl2 H2 O], [L = 2, 6-bis(5- tert -butyl-1 H -pyrazol-3-yl)pyridine (for Os1 ), 2, 6-bis(5- tert -butyl-1-methyl-1 H -pyrazol-3-yl)pyridine (for Os2 ) or 2, 2′:6′, 2′′-terpyridine (for Os3 )]. Single crystal X-ray analysis of a DMSO adduct of complex Os1 was performed. Kinetics of substitution reactions of examined Os1–3 complexes with biomolecules 5-GMP, l -Met, and GSH were followed in the presence and absence of different biocompatible ionic liquids. Binding properties of the examined complexes to biologically important molecules, CT-DNA and HSA, were investigated using UV-Vis spectrophotometry, fluorescence spectroscopy, and gel electrophoresis. Interactions with CT-DNA were performed both in the absence and presence of biocompatible ionic liquids. To locate the binding site and possible binding mode of the examined complexes to CT-DNA and HSA, fluorescence competition experiments with site-markers were performed. To better understand these interactions and obtain detailed binding information of the examined complexes with CT-DNA, and HSA, molecular docking studies and fluorescence resonance energy transfer (FRET) were performed. In vitro cytotoxicity and redox status experiments on three cancer cell lines and on one healthy cell line were performed to elucidate the possible molecular mechanisms of investigated Os1–3 complexes.